Correlation of articular involvement, skin disfigurement and unemployment with depressive symptoms in patients with systemic sclerosis: a hospital sample. (29th May 2013) - Tedeschini, Enrico; Pingani, Luca; Simoni, Elena; Ferrari, Daniela; Giubbarelli, Cinzia; Giuggioli, Dilia; Lumetti, Federica; Rigatelli, Marco; Ferri, Clodoveo; Ferrari, Silvia
Abstract Background Systemic sclerosis (SSc) is a connective tissue disease associated with increased functional impairment, body image distress due to skin lesions, and psychosocial comorbidity, particularly depression. Prevalence of depressive symptoms in SSc patients ranges from 36% to 65% and it contributes to the worsening of any aspect of the disease. The aim of this study was to investigate the prevalence and clinical and non‐clinical correlates of depressive symptoms in a sample of outpatients with SSc. Methods Seventy‐eight consecutive SSc outpatients were recruited from February 2005 to July 2007. Socio‐demographic and SSc‐related clinical data were collected, including a modified Rodnan Skin Score, the Valentini Disease Activity Index and psycho‐metric assessment of disability and pain. Depressive symptoms were assessed using the Beck Depression Inventory (BDI). Two questions on perception of support from relatives and impact of disfigurements were also directly addressed to subjects. Results The BDI mean score was 10.5 (± 8.3), with 36 subjects (46.2%) scoring above clinical significance. Unemployment, increased disability, pain, disease activity and articular involvement were significantly associated with more depressive symptoms. Older age, unemployment and more depressive symptoms were also related with complaints of disfigurements due to skin involvement. Conclusions Depression is an influential prognostic factor in SSc. The present study contributes to the knowledge of the relationship between depression and clinical features routinely collected in rheumatology settings in order to develop a standardized assessment of psychosocial distress in routine rheumatologic procedures.